35 Year achievements of Brazilian Oral Research - Rode, Sigmar de Mello [UNESP]; Paiva, Saul Martins (FapUNIFESP (SciELO), 2021)
This editorial addresses the history of Brazilian Oral Research (BOR), official journal of the Brazilian Division of the International Association of Dental Research (SBPqO). BOR is increasingly consolidating itself as the most important journal in Brazilian dental research. However, much still needs to be done. The hard and continuous work to improve the journal will guarantee its permanent growth and result in new achievements for the benefit of the entire dental scientific community.